2014
DOI: 10.1088/0004-637x/786/2/100
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength Observations of the Candidate Disintegrating Sub-Mercury Kic 12557548b, ,

Abstract: We present multiwavelength photometry, high angular resolution imaging, and radial velocities, of the unique and confounding disintegrating low-mass planet candidate KIC 12557548b. Our high angular resolution imaging, which includes spacebased HST/WFC3 observations in the optical (∼0.53 µm and ∼0.77 µm), and groundbased Keck/NIRC2 observations in K'-band (∼2.12 µm), allow us to rule-out background and foreground candidates at angular separations greater than 0.2 ′′ that are bright enough to be responsible for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 38 publications
8
93
0
Order By: Relevance
“…Rappaport et al (2012) announced KIC 12557548b (KIC 1255b for short), an apparently evaporating planet with a 16 hr period discovered with the Kepler observatory. Consistent with Arnold's prediction, its transit depths vary, even between consecutive transits "from a maximum of 1.3% of the stellar flux to a minimum of 0.2% or less without a discernible rhyme or reason" (Croll et al 2014). Further, Figure 1 shows how the transit light curves "exhibit[] an obvious ingress/egress asymmetry, with a sharp ingress followed by a longer, more gradual egress" (Croll et al 2014) consistent with Forgan's model.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…Rappaport et al (2012) announced KIC 12557548b (KIC 1255b for short), an apparently evaporating planet with a 16 hr period discovered with the Kepler observatory. Consistent with Arnold's prediction, its transit depths vary, even between consecutive transits "from a maximum of 1.3% of the stellar flux to a minimum of 0.2% or less without a discernible rhyme or reason" (Croll et al 2014). Further, Figure 1 shows how the transit light curves "exhibit[] an obvious ingress/egress asymmetry, with a sharp ingress followed by a longer, more gradual egress" (Croll et al 2014) consistent with Forgan's model.…”
supporting
confidence: 71%
“…Croll et al (2014) observed the target in ¢ K band ( m2.15 m) at CFHT simultaneously with Kepler (in the broadband optical near 0.6 mm) and found no wavelength difference (the depth ratio between the two bands was 1.02 ±0.2).…”
Section: Diagnosing Kic 12557548-like Objects As Artificialmentioning
confidence: 98%
See 2 more Smart Citations
“…Rappaport et al (2012) discovered a transiting disintegrating exoplanet KIC12557548b with a comet-like dusty tail extending well beyond its Hill radius and featuring a pre-transit brightening. Recent studies have shown that pre-transit brightening is due to strong forward scattering and can be used, together with the color dependence of the transit depth, to constrain the particle size of dust grains in the comet-like tail, which was found to be of the order of 1 micron (Budaj 2013;Croll et al 2014;Bochinski et al 2015) (see also Brogi et al 2012;van Werkhoven et al 2014). Two other objects of this kind (KOI-2700b, EPIC201637175B) have been discovered already by Rappaport et al (2014) and Sanchis-Ojeda et al (2015).…”
Section: Introductionmentioning
confidence: 99%